Premorbid knee osteoarthritis is not characterised by diffuse thinness: the Framingham Osteoarthritis Study. Issue 11 (24th January 2008) - Hunter, D J; Niu, J B; Zhang, Y; LaValley, M; McLennan, C E; Hudelmaier, M; Eckstein, F; Felson, D T
Abstract : Objective: It is hypothesised that, like low bone density and fracture, thin cartilage predisposes to osteoarthritis (OA). Inferences about the effects of cartilage thickness on the development of OA can be made by evaluating the status of an unaffected non-diseased contralateral knee, in persons with unilateral OA, which we shall label the "premorbid knee". The primary objective of this analysis was to compare cartilage thickness in premorbid knees with non-OA knees drawn from persons without any knee OA to determine if cartilage in the premorbid knee was thinner than in the knee drawn from someone without OA in either knee. Methods: From 2002 to 2005, The Framingham Osteoarthritis Study recruited subjects without respect to OA from the community. We obtained posteroanterior, semiflexed and lateral films of both knees and knee magnetic resonance imaging to quantify cartilage volume in one knee. The cartilage plates of the patella, medial and lateral femur, medial and lateral tibia were quantified, using a 3D FLASH-water excitation sequence (in plane resolution 0.3×0.3 mm, 512 matrix, slice thickness 1.5 mm) and digital post-processing, involving three-dimensional reconstruction. Radiographs were used to define the OA status of knees with disease defined as Kellgren and Lawrence grade ⩾2 and or patellofemoral OA on the lateral film. Of 1020 participants included in this analysis, 720 had no OA in either knee (no-knee OA sample), and 55 subjects had no OA in the knee that was examined using magnetic resonance imaging and OA in the contralateral knee (premorbid knee OA sample). We compared cartilage thickness and percentage of cartilage coverage (total bone interface covered with cartilage) between these groups. After initial plate-specific univariate comparisons we performed a multiple regression to assess the association between OA status (premorbid versus no OA knee) and cartilage thickness adjusting for age, sex and body mass index. We used the Generalised Estimating Equation to account for correlation between plates. To further determine if the cartilage was diffusely thinned or had only increased areas of denuded cartilage, we removed plates with denuded areas (less than 95% cartilage coverage) from the analysis. Results: 55% of subjects were women. There was no difference in cartilage thickness between the premorbid knees and the no-knee OA sample. After adjusting for age, sex and body mass index and removing plates with less than 95% coverage from the analysis, we found the same or even thicker cartilage in premorbid knees compared with the knee OA sample. Conclusions: Premorbid knees do not have diffuse cartilage thinness. Rather the cartilage is normal or thicker with denuded areas suggesting that this may be the initial pathology rather than diffuse thinning.